An implementation of distributed and HTTP-based geological petroleum data web service with RESTful architecture. Issue 6 (2nd November 2017) - Peng, Shijie; Zhang, Zhiting; Wu, Chonglong; Liu, Gang
Abstract: It researches how to build a distributed data service platform based on REST architecture in the digital oilfield. In oil enterprise, the data are scattered in the isolated system among various department. Due to the management issue, all the database and interface standards and technologies of departmental system are incompatible to each other. With the continuous expansion of exploration and research, the demand for enterprise data integration platform is tremendous increased. In this paper, we propose a data integration based on REST style data interface. It focuses on the REST interface with HATEOAS constraint and the distributed transaction model driven by REST interface. The data integration platform specifically has solved the sharing and integration issues as well as the transactional problem across heterogeneous system in the oilfield enterprise.